Tumor Cell/Dendritic Cell Interactions and the Influence of Tumors on Dendritic Cell-mediated Anti-Tumor Immune Responses and Dendritic Cell-Based Tumor Immunotherapies - Timothy Bullock (Frontiers Research Topics, 2014)
Significant efforts over the last two decades have been made to better understand the factors that control DC maturation and activation and the impact of these processes on overall host immunity. In addition to the well-characterized role of DC in the induction of immunity to pathogens, a role for these cells as critical regulators of anti-tumor immune responses has more recently become apparent. These findings have generated interest in understanding how tumor/DC interactions impact the quality of anti-tumor immune responses, and they have contributed to increased enthusiasm for a variety of DC-based cancer immunotherapies. Such strategies have included DNA- or peptide-based vaccines that involve uptake and processing of tumor antigens by endogenous DC in cancer patients or the administration of tumor antigen-loaded exogenous DC-based vaccines. Additionally, many adjuvant, cytokine, and monoclonal antibody therapies aim either to enhance the immunostimulatory capacity of endogenous DC or to supplement the activity of these cells by targeting costimulatory receptors on T cells. Despite the promise of such therapeutic approaches for cancer treatment, their success is often limited, and much remains to be understood about how tumors influence DC function and the quality of DC-mediated immune responses. Tumor/DC interactions have therefore become an increasingly active area of investigation, and many studies have described effects of tumors on DC phenotype and function that include an accumulation of immature DC within tumors, tumor-altered differentiation of DC precursors into myeloid-derived suppressor cells, and the generation of tumor-associated DC with immunoregulatory properties. As this field moves forward, it will be important to gain mechanistic insights into the basis for both tumor-mediated DC dysfunction as well as the induction of either suboptimal or immunosuppressive adaptive anti-tumor immune responses by tumor-associated DC. Progress in these areas of tumor immunology will greatly improve our understanding of the factors that contribute to effective DC-mediated anti-tumor immune control versus DC-associated anti-tumor immune dysfunction and subsequent tumor immune escape. Such information is vital for improving current and developing novel immunotherapeutic strategies for interfering with tumor-associated DC dysfunction and enhancing the functional quality of endogenous DC in cancer patients as well as the efficacy of exogenous DC-based anti-tumor vaccines. The articles contained within this special issue highlight these important topics and bring focus not only to our current understanding of tumor/DC interactions but also to major areas of investigation that remain ongoing in this field.